A theory of musical narrative - Almén, Byron (Bloomington Indiana University Press, 2008)
This comprehensive volume offers a wide-ranging perspective on the stories that art-music has told since the start of the 20th century. Contributors challenge the broadly held opinion that the loss of tonality in some music after 1900 also meant the loss of narrative in that music. On the contrary, the editors and the essayists in this book demonstrate how experiments in approaching narrative in other media, such as fiction and cinema, suggested fresh possibilities for musical narrative, which composers were quick to exploit. The new conceptions of time, narrative voice, plot, and character that accompanied these experiments also had a significant impact on contemporary music. The repertoire explored in the collection ranges across a wide variety of genres and includes composers from Charles Ives and the Pet Shop Boys to Thomas Adès and Dmitri Shostakovich.